2012
DOI: 10.2169/internalmedicine.51.8149
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent <i>Helicobacter cinaedi</i> Cellulitis and Bacteremia in a Patient with Systemic Lupus Erythematosus

Abstract: A 31-year-old woman who had developed systemic lupus erythematosus at 17 years of age was admitted to the hospital for suspected cellulitis in the lower extremities. A blood culture performed upon admission to the hospital detected Helicobacter cinaedi (H. cinaedi), which was also isolated in blood and fecal cultures obtained on the 42nd hospital day. Bacterial translocation of H. cinaedi present in the intestines may have led to the development of recurrent bacteremia and cellulitis. In cases such as this, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…H. cinaedi might have presented as transient bacteremia in immunocompromised patients, especially in the 27 patients with only fever. Also, recent studies suggested that H. cinaedi may cause recurrent bacteremia (12)(13)(14), which was reported in 15 patients (24%) in the current study. The reason recurrent bacteremia occurs in specific cases remains unknown; however, H. cinaedi in the gastrointestinal tract may be associated with recurrent bacteremia.…”
Section: Discussionsupporting
confidence: 64%
“…H. cinaedi might have presented as transient bacteremia in immunocompromised patients, especially in the 27 patients with only fever. Also, recent studies suggested that H. cinaedi may cause recurrent bacteremia (12)(13)(14), which was reported in 15 patients (24%) in the current study. The reason recurrent bacteremia occurs in specific cases remains unknown; however, H. cinaedi in the gastrointestinal tract may be associated with recurrent bacteremia.…”
Section: Discussionsupporting
confidence: 64%
“…In common with other intestinal pathogens, EHS have been found to translocate resulting in bacteremia and other secondary infections such as cellulitis and arthritis (reviewed in O' Rourke et al 2001;Fox 2002;Solnick 2003;Freeman and Holland 2007;Minauchi et al 2010;Kikuchi et al 2012;Rimbara et al 2012). While H. cinaedi is the predominant organism identified in these infections other cases have been attributed to H. bilis (previously referred to as flexispira), H. fennelliae and more recently H. canis (Leemann et al 2006;Alon et al 2010;Turvey et al 2012).…”
Section: Enterohepatic Infectionsmentioning
confidence: 99%
“…H. cinaedi and H. fennelliae also cause bacteraemia in patients with chronic renal failure, autoimmune diseases and solid organ cancers (Nishine et al , 2007; Matsumoto et al , 2007; Rimbara et al , 2013b; Saito et al , 2016). There are several reports of recurrent H. cinaedi bacteraemia in immunocompromised hosts (Sullivan et al , 1997; Mammen et al , 1995; Kikuchi et al , 2012; Uçkay et al , 2006), which is treated with prolonged antibiotic therapy to prevent further recurrence (Kiehlbauch et al , 1994; Tee et al , 1996; Sullivan et al , 1997). However, only a few cases of recurrent H. fennelliae bacteraemia have been reported in Japan (Saito et al , 2016), and there are no guidelines regarding the choice or duration of antimicrobial treatment and prevention of recurrence for H. fennelliae infection.…”
Section: Introductionmentioning
confidence: 99%